Branch-switching procedure for post-buckling analysis of thin-walled steel members at elevated temperature. (March 2019) - Possidente, Luca; Tondini, Nicola; Battini, Jean-Marc
Abstract: The paper investigates the effects of the geometrical imperfections in buckling analyses of plated steel elements at elevated temperatures and provides an alternative branch-switching procedure to perform post-buckling analyses without introducing initial imperfections into the model. This procedure is appealing since the choice of appropriate imperfections in classical analyses is not straightforward, above all at elevated temperature. Several numerical analyses show that the choice of the imperfections is not trivial and that the buckling mode may vary with temperature. They also show that the proposed branch-switching procedure is an interesting preliminary tool to understand the instability behaviour of steel structural members. Highlights: Buckling of compressed steel plated elements at elevated temperatures is studied. A branch-switching procedure performed without introducing imperfections is proposed. The procedure is an interesting preliminary tool to study the post-buckling behaviour. Linear buckling analyses may not capture the buckling mode at high temperature. Imperfections based on modes at ambient temperature do not always give safe results.